2010
DOI: 10.1016/j.toxicon.2010.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the activation pathway of the T-type calcium channel CaV3.1 by ProTxII

Abstract: Toxins have been used extensively to probe the gating mechanisms of voltage-gated ion channels. Relatively few such tools are available to study the low-voltage activated T-type Ca channels, which underlie thalamic neuron firing and affect sleep, resistance to seizures, and weight gain. Here we show that ProTxII, a peptide toxin recently isolated from the venom of the tarantula spider Thrixopelma pruriens, dose-dependently inhibited Ca V 3.1 causing a decrease in current (81.6% ± 3.1% at −30 mV in 5 μM toxin) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 45 publications
1
22
2
2
Order By: Relevance
“…Contrary to previous findings [18], ProTx II appeared to preferentially block hCav3.2. This toxin block caused a significant negative shift in half inactivation voltage of hCav3.2, but in contrast with previous studies on sodium and calcium channels, no significant change in half activation potential [18,30,31]. The apparent differences between some of our results and those of previous studies, may be in part be due to the different expression systems, recording methods and clones used.…”
Section: Resultscontrasting
confidence: 99%
“…Contrary to previous findings [18], ProTx II appeared to preferentially block hCav3.2. This toxin block caused a significant negative shift in half inactivation voltage of hCav3.2, but in contrast with previous studies on sodium and calcium channels, no significant change in half activation potential [18,30,31]. The apparent differences between some of our results and those of previous studies, may be in part be due to the different expression systems, recording methods and clones used.…”
Section: Resultscontrasting
confidence: 99%
“…Both peptides were subsequently shown to block Ca V 3 channels in a subtype-dependent manner (Edgerton et al, 2010). Protoxin I preferentially blocks Ca V 3.1 channels over Ca V 3.3 and even more so over Ca V 3.2 (Ohkubo et al, 2010;Bladen et al, 2014b).…”
Section: Ca V 3 Channel Pathophysiologymentioning
confidence: 99%
“…Protoxin I preferentially blocks Ca V 3.1 channels over Ca V 3.3 and even more so over Ca V 3.2 (Ohkubo et al, 2010;Bladen et al, 2014b). Protoxin II appears to act as a gating modifier, with the highest affinity for Ca V 3.2 channels (Edgerton et al, 2010;Bladen et al, 2014b). Another spider toxin that blocks T-type calcium channels is PsPTx3, a peptide isolated from Theraphosidae tarantula that has apparent selectivity for Ca V 3.2 calcium channels (French patent application FR2940973).…”
Section: Ca V 3 Channel Pathophysiologymentioning
confidence: 99%
“…Recent studies identified other toxins ( e.g. , ProTx-I and ProTx-II) that inhibit T-type channels 153; 154 . However, their affinity and effects on channel gating are different compared with those of kurtoxin.…”
Section: Voltage-gated Calcium Channel Toxinsmentioning
confidence: 99%